Preventing The Spread of Radicalization And Extremist Ideas Among Youth Is A Demand of Our Time - Saminov, Elyorjon (Pubmedia Social Sciences and Humanities, 2025)
This study examines modern strategies for preventing youth radicalization and the spread of extremist ideologies. The research focuses on the socio-political and psychological factors contributing to radicalization and explores various deradicalization efforts. The methodology includes a review of international counter-radicalization programs and case studies of successful prevention initiatives. The findings indicate that a multi-sectoral approach involving education, social engagement, and community resilience-building is essential in combating radical ideologies. The study emphasizes the need for early intervention and the role of government and civil society in addressing these challenges.